The First (13th) Lithuanian Police Battalion and the Killing of Jews in 1941 - Bubnys, Arūnas (Genocidas ir rezistencija, 2006)
The objective of this study is to show the role the National Labour Protection Battalion in the 1941 killings of Jews. The author seeks answers to these questions: Which companies and detachments of the battalion took part in the killings? Where and when did they kill Jews? What is the approximate number of Jews the battalion exterminated? How many officers and soldiers from the battalion participated?The 3rd company of the 1st Police Battalion (the core of J. Hamann's “flying” detachment) was very active in the policy of the Holocaust organised by the Nazis. The number of Jews exterminated by the battalion can be compared only to those exterminated by the German Secret Police and the SD special detachment in Vilnius, or the 2nd (12th) Battalion of the Lithuanian Police. In 1941, the 1st Battalion of the Lithuanian Police, together with the German Gestapo and auxiliary policemen (baltaraiščiai), exterminated not less than 36,000 Lithuanian Jews and others brought from abroad (from Austria, Belarus, the Czech Republic and Germany). About 23,000 were killed in Kaunas, about 11,600 in other places in Lithuania, and about 1,400 in Belarus. If it is true that the 3rd Company of the 1st Battalion operated in almost all the sites mentioned in K. Jäger's account (except for the Vilnius and Šiauliai districts), then the number of Jews killed will be considerably higher.Direct killings were carried out by the 3rd Company, and partly by the 1st Company (which operated in Kaunas' 7th Fort on 4 July 1941). The author's calculations show that 104 officers, sergeants and soldiers from the 3rd Company took part in the shootings. In one way or another (including shootings, bringing to the sites, guarding them, and guarding the ghetto and the forts) most of the battalion was involved in the Holocaust (the 1st, 2nd and 3rd companies).
Keywords: German occupation; Jews; Holocaust; Second World War; police batallions